Answer:
The missing value is(0,0)
Step-by-step explanation:
The complete question is:
2x+3y=5x-y
Complete the missing value in the solution to the equation.
( ,0)
<u>Solution:</u>
We have given:
2x + 3y = 5x - y
Combine the like terms:
2x-5x= -y-3y
-3x = -4y
Both negative signs will be cancelled out by each other.
So we have,
3x = 4y
We have given y = 0
Then
3x = 4*0
3x= 0
Divide both sides by 3
3x/3 = 0/3
x = 0
y=0
Therefore missing value is(0,0)
Answer: 8%
Step-by-step explanation:
the answer is 7.5% but you said its a whole number so i guess its 8%
Answer:
4
Step-by-step explanation:
Answer:
8y^3+6y^2-29y+15
Step-by-step explanation:
the correct expression is
(4y − 3)(2y^2 + 3y − 5)
Given data
We have the expression
(4y − 3)(2y^2 + 3y − 5)
let us open bracket
8y^3+12y^2-20y-6y^2-9y+15
Collect like terms
8y^3+12y^2-6y^2-20y-9y+15
8y^3+6y^2-29y+15